Analisis Konsep Akhlak Terhadap Diri Sendiri: Studi Pada Siswa Kelas IX MTs Fastabiqul Khairat Kolaka Timur - Risal Fratama; Waharjani Waharjani (Innovative: Journal Of Social Science Research, 2023)
Not a few students of class IX MTS. Fastabiqul Khairat who consciously does not routinely maintain cleanliness around his class environment. In addition, if the teacher does not instruct students to keep the class clean, the students do not do it independently. This proves that there is a lack of morals towards oneself even though in theory class IX has learned a lot related to morals. Therefore, the purpose of this study is to analyze the concept of morality towards oneself in class IX students. The method of this research is descriptive qualitative with the application of field studies using interviews, observation, and documentation. The results of this study found three concepts of morality towards oneself including; 1). Morals to the body. 2). Morals to the soul and 3). Morals to thoughts.